(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the frequency of hyperuricemia (HU) with ischemic and hypertensive cardiac disease. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Dept. of Medicine at Khyber Teaching Hospital (KTH ) Peshawar from November 2022 to February 2023. Materials and Methods: Sixty study samples were collected from cardiology and the different medical wards of KTH. After the recruitment of subjects according to the inclusion criteria, subjects underwent phlebotomy for serum uric acid. The data was then organised and analysed in SPSS software version. 26. Results: Out of the sixty subjects included in the study, 35 subjects were males while 25 were females. Subjects had a mean age of 55.4 ± 4 years. 26 patients had HU while 34 patients had ischemic or hypertensive cardiac disease in the absence of raised uric acid levels. Out of 35 males, 11 males had hyperuricemia. Whereas out of 25 females, 9 had HU. HU was observed in 40% of the ischemic heart disease patients and 45% of the hypertensive heart disease patients. Conclusion: Our study concludes that there is high frequency of HU among patients with ischemic and hypertensive heart disease. This indicates a high disease burden of HU patients.